Maribacter cobaltidurans sp. nov., a heavy-metal-tolerant bacterium isolated from deep-sea sediment - Fang, Chen; Wu, Yue-Hong; Xamxidin, Maripat; Wang, Chun-Sheng; Xu, Xue-Wei (International journal of systematic and evolutionary microbiology, 2017)
A Gram-stain-negative, aerobic, non-motile and rod-shaped bacterium, designated B1 , was isolated from deep-sea sediment collected from the South Atlantic Ocean. Cells of strain B1 grew in medium containing 0.5-6.0 % (w/v) NaCl (optimum 1.0-2.0 %), at pH 5.5-7.5 (optimum pH 7.0) and at 15-37 °C (optimum 30 °C). Aesculin, starch and Tweens 20, 40 and 60 were hydrolysed. The strain was able to grow in medium containing a high concentration of Co (10 mM). The 16S rRNA gene sequence of strain B1 shared high similarity with respect to Maribacter orientalis DSM 16471 (97.7 %), and exhibited less than 97.0 % sequence similarity with the type strains of other species with validly published names. Phylogenetic analyses revealed that strain B1 fell within the cluster comprising Maribacter species and formed an independent lineage. The average nucleotide identity and in silico DNA-DNA hybridization values between strain B1 and M. orientalis DSM 16471 were 72.0 % and 17.6 %, respectively. Strain B1 contained menaquinone 6 (MK-6) as the sole isoprenoid quinone and iso-C17 : 0 3-OH, iso-C15 : 0 and iso-C15 : 1 G as the predominant cellular fatty acids. The major polar lipids were phosphatidylethanolamine, one unidentified aminolipid and two unidentified lipids. The DNA G+C content was 39.7 mol%. According to the phylogenetic, chemotaxonomic and phenotypic data, B1 represents a novel species of the genus Maribacter, for which the name Maribacter cobaltidurans sp. nov. is proposed. The type strain is B1 (=CGMCC 1.15508 =KCTC 52882 =MCCC 1K03318 ).